The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.2478/s11535-008-0019-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of low molecular weight advanced glycation end products and nitric oxide metabolites with chronic complications in type 1 diabetic patients

Abstract: Advanced glycation end products (AGEs) are involved in the occurrence of vascular complications in diabetes. The present study was undertaken to investigate the level of low-molecular weight products of AGEs (LMW-AGEs) in relation to microvascular complications in type 1 diabetes, and the possible relationship with nitric oxide (NO) as a marker of endothelial function. Patients with normal renal function (NRF) were classified into two groups: (1) without, and (2) with diabetic neuropathy; and patients with ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
1
8
0
Order By: Relevance
“…It is evident that NO plays a regulatory role in the peripheral nervous system [7], and recent reports have indicated that excessive local NO levels are present at sites of diabetic neuropathy [8]. Recently we showed a significant correlation between NO metabolites and LMW-AGEs and diabetic neuropathy in T1DM [9].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…It is evident that NO plays a regulatory role in the peripheral nervous system [7], and recent reports have indicated that excessive local NO levels are present at sites of diabetic neuropathy [8]. Recently we showed a significant correlation between NO metabolites and LMW-AGEs and diabetic neuropathy in T1DM [9].…”
Section: Introductionmentioning
confidence: 63%
“…We previously used this T1DM group to estimate the relationship between LMW-AGEs and diabetesassociated microvascular complications; this study reported details on body mass index, fasting blood glucose, total cholesterol, triglycerides, HbA1c, systolic and diastolic blood pressure, and serum creatinine clearance [9].…”
Section: Study Groupsmentioning
confidence: 99%
“…Hyperglycemia, the primary clinical manifestation of diabetes, contributes to diabetic complications [1] by inducing vascular inflammation, oxidative stress, impaired vascular relaxation, changing vascular cell metabolism, altering the vascular matrix molecules, and circulating proteins/lipoproteins. [2][3][4] Nevertheless, the precise mechanisms by which hyperglycemia induce pathological outcomes and the molecular nature of its downstream effectors is still a debatable issue.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon occurs early in the natural course of diabetes and independently of the presence of microvascular complications. So, we suggest that the high NO levels found in diabetic patients (including those without any clinically manifested microangiopaties) might represent an overproduction of NO that is associated with diffuse endothelial dysfunction (Heltianu et al, 2008). There is a family of NOS enzymes which produces NO.…”
Section: Nitric Oxide Synthase Genesmentioning
confidence: 90%
“…In active progressive DR, aqueous NO levels are significantly high, while plasma NO levels remained at the level of diabetics without DR (Yilmaz et al, 2000). Raised plasma NO levels in T1DM patients were reported (Heltianu et al, 2008) indicating that pathogenesis of diabetic-associated vascular complications is connected with a generalized increased synthesis of NO throughout the body. This phenomenon occurs early in the natural course of diabetes and independently of the presence of microvascular complications.…”
Section: Nitric Oxide Synthase Genesmentioning
confidence: 99%